GRADE ANKLE BRACHIAL INDEX (ABI) AS A PREDICTOR OF PERIPHERAL ARTERY DISEASE (PAD) IN MELLITUS PATIENTS - Rahmawati, Ima; Yogha, Kend Ramadio Rimba Syah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
Peripheral Artery Disease (PAD) often occurs in diabetes mellitus patients. PAD can be detected early by measuring the Ankle Brachial Index (ABI). ABI measurement should be important for all DM clients and all clients at risk of DM but is often ignored, causing PAD. The purpose of this study was to determine the Ankle Brachial Index (ABI) as a predictor of Peripheral Artery Disease (PAD) in patients with diabetes mellitus. The design of this study was descriptive with an observational study approach. The population in this study were all 113 diabetes mellitus clients in July 2024. The sampling technique used purposive sampling so that 100 people were obtained who met the inclusion and exclusion criteria. The research instrument used a digital tensiometer and observation sheet. Data analysis used frequency distribution. The results showed that the normal ankle brachial index value was 40 people (40%), respondents who experienced moderate PAD were 28 people (28%), mild PAD 16 people (16%), ABI tolerated 15 people (15%), and hardening of the arteries 1 person (1%). Data analysis suggested that almost half of the respondents had ankle brachial index PAD values ​​consisting of moderate PAD and mild PAD. Moderate PAD occurs in obese diabetes mellitus patients and those who have suffered from diabetes mellitus > 5 years, and mild PAD occurs in those who have suffered from diabetes mellitus > 5 years and have a history of hypertension.